파빌리온의 경량화 구축 특성에 관한 연구 - MoMa P.S.1 젊은 건축가 프로그램(YAP)의 우승작을 중심으로 - - 김진재; 전유창; 김성욱 (교육시설, 2019)
This study embody the investigation of the winner projects of Young Architecture Program(YAP) taken place annually at front yard of MoMA PS1 since 1998. Every installation of project is experimental exhibition that have ambiguous border in the area between lightness and architecture. Thus the design have less limits as architectural space and talents can express the innovative idea strong. This paper aims to probe annual significant key words by analyzing the contemporary representative space types, materials, fabrication methods and innovative ideas, and to identify the changes of important concept of lightness and recent trend in architect design concept.
Keywords: 경량화; 파빌리온; 구축; 재료; 구조; 결합; Lightness; Pavilion; Tectonic; Material; Structure; Fabrication